ENVIRONMENTAL HEALTH IN THE 21ST CENTURY:ISSUES, CHALLENGESANtJ PROSPECTS. - L. A. BRIGGS, BRIGGS (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
Environmental Health in a discipline in Public Health whose focus is on the . promotion and maintenance of Healthy Environment for the survival of humanity. Environmental Health has been defined by The World Health organisation (WHO) (1992) as been the "control of all those factors in the physical environment that exercise or may exercise a deleterious effect on physical development, health’ and survival." This far reaching definition encompassesa very wide range of activities and involves the work of many different disciplines. Environmental Health is the study of how environmental factors can harm health and how to identify, prevent and control such effects.